Pendampingan Penelitian Berbasis Artificial Intelligence: Eksplorasi Peluang dan Tantangan Metodologis dalam Penelitian Akademik Mahasiswa - Muaripin, Ary Maulana; Aminuddin, Muhammad; Muaripin; Muaripin, Muhammad Hanif Al-Haya (Paedagogie, 2026)
The rapid advancement of Artificial Intelligence (AI) has transformed the way university students conduct academic research, ranging from literature searching to research methodology development. Despite its growing adoption, limited studies have explored how AI influences students' methodological understanding throughout the research process. This study aimed to explore the opportunities and methodological challenges of AI-assisted research among university students. A qualitative descriptive approach was employed involving 22 participants, consisting of 15 undergraduate students and 7 postgraduate students who were preparing research proposals, theses, or scholarly articles. Data were collected through semi-structured interviews and document analysis and analyzed using Thematic Analysis. The findings revealed that AI significantly improved research efficiency by facilitating literature exploration, methodological development, idea generation, and academic writing. However, several methodological challenges were identified, including unreliable references, inconsistent methodological recommendations, and students' tendency to rely on AI without verifying primary scholarly sources. These findings indicate that AI should be positioned as a research assistant rather than a substitute for students' scientific reasoning. This study contributes to research methodology instruction and provides recommendations for the ethical and responsible integration of AI in higher education.